A study of effects of anemia on maternal and perinatal outcomes - Prakash, Som; Kandoria, Meenakshi; Pal, Anita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: The objective of the study was to evaluate the prevalence of anemia in antenatal women and to assess the effects of anemia on maternal and perinatal outcomes. Methods: A cross sectional observational study was conducted on 1000 random patients admitted in the labour room. Results: Anemia was found in 687 patients (68.7%) at the time of delivery. Nearly 321 (46.72%) had mild, 349 (50.80%) had moderate and 17 (2.47%) had severe anemia. About 72% subjects were from 20-30 years age group, 77.7% belonged to rural area, 87.8% were, booked cases. A total of 81% had received iron folic acid prophylaxis, 63.2%, belonged to lower socioeconomic class, 91.2% were educated upto primary school and 47.7% were primigravida There were significant differences in prematurity, birth weight and hypertensive disorders of pregnancy between anemic and non anemic groups. About 20.4% of anemic patients had complications like Intra uterine growth retardation (IUGR), gestational hypertension, preeclampsia, eclampsia. Nearly 91.30% IUGR were anemic and all patients with preeclampsia, eclampsia and hemolysis elevated liver enzymes, and low platelet count (HELLP) syndrome had anemia. Low appearance, pulse, grimace, activity, and respiration (APGAR) score and increased incidence of admission to Neonatal Intensive Care Unit was seen in babies born to anemic mothers. Conclusions: Maternal anaemia is associated with increased risks of postpartum haemorrhage, low birthweight, small-for-gestational age babies and perinatal death. While the best approach is prevention, a large number of women present with severe anaemia late in pregnancy. Since there is no clear guidance on how these women should be managed during labour and delivery, therefore, this issue needs to be addressed urgently.